(Na0.74Ag1.26)BaSnS4: A New AgGaS2‐Type Nonlinear Optical Sulfide with a Wide Band Gap and High Laser Induced Damage Threshold. Issue 61 (31st August 2022) - Zhou, Wenfeng; Liu, Wenlong; Guo, Sheng‐Ping
Abstract: The development of high‐power solid‐state lasers is in urgent need of infrared (IR) nonlinear optical (NLO) materials with wide band gaps and high laser‐induced damage thresholds (LIDTs). Herein, a new compressed chalcopyrite‐like IR NLO crystal (Na0.74 Ag1.26 )BaSnS4 was successfully synthesized using a facile high‐temperature solid‐state method. Its structure can be considered as a variant of chalcopyrite AgGaS2 (AGS)‐type ones. It features a three‐dimensional framework constructed by corner‐sharing [(Na/Ag)S4 ] 7− ∞ layers and isolated SnS4 tetrahedra with negative cavities occupied by counter ion Ba 2+ . (Na0.74 Ag1.26 )BaSnS4 exhibits phase‐matchable moderate SHG response (0.31 × AGS), wide band gap (3.70 eV), and high LIDT (6.44 × AGS). Theoretical calculations reveal that the NLO response of (Na0.74 Ag1.26 )BaSnS4 is mainly originated from the synergetic effects of AgS4 and SnS4 tetrahedra, and the inclusion of alkaline and alkaline earth metals is responsible for the wide band gap and high LIDT. Moreover, the discovery of this chalcopyrite‐like compound will provide a feasible design strategy for the exploration of new promising IR NLO materials. Abstract : A new AgGaS2 ‐type sulfide (Na0.74 Ag1.26 )BaSnS4 with compressed chalcopyrite‐like structure was obtained. It exhibits balanced NLO properties, including moderate SHG response, wide band gap, and high LIDT.